Aseguramiento de la integridad del cable de perforación mediante el diseño de una herramienta digital para el cálculo de la variable tonelada-milla en operaciones de perforación y workover de la compañía Estrella International Energy Services. (2020)
It is essential for companies in the oil sector to reduce costs without putting operations, human lives, and equipment at risk. The drilling line is a critical element in the drilling and maintenance of wells, given the eventuality of the cable breaking due to inefficient control, it could generate from great economic losses due to damage to equipment to loss of human life. In this project, an effective method is presented to be able to carry out a total insurance to the drilling line, extending its useful life to the maximum reducing costs, without putting human lives and the integrity of the equipment at risk. For this, a study of the operations and specifications of the equipment that affect the integrity of the wire rope was carried out, taking as reference the IADC standards, API RP 9B, API SPEC 9A, API RP 54, ISO 4309 and manufacturer's recommendations, where It showed that for the correct performance of the wire rope, the condition of the equipment lifting system is essential, which is why it was evaluated on 4 equipment and from visual, dimensional inspections and non-destructive tests to rule out premature damage due to mechanical conditions where it was concluded that all the elements of the lifting system are within the regulations and do not add mechanical wear to the wire rope.